Sociolinguistic accommodation of Romanian immigrants to the local norm: the intervocalic /d/ - Svetozarovová, Radka; Cruz Ortiz, Rocío (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This paper presents a Spanish sociophonetic study of intervocalic /d/ in speakers of Romanian origin living in the province of Granada (Spain). The behavior of this consonant between vowels is not homogeneous in the Hispanic world, and this research will try to determine to which variety of Spanish the Romanian immigrants settled in Granada are accommodated as far as this phenomenon is concerned: the Andalusian or the Castilian variety. The results reveal that the informants are divided into two distinct groups: those who support elision and those who clearly disfavor it. The analysis has allowed us to establish that, in general, the patterns followed by Romanian speakers are very similar to those of the vernacular population of Granada and not so much to those of the central-northern speakers, but with considerably lower percentages of elision. Among the causes, it is social factors, rather than linguistic ones, which determine one or the other choice, especially the occupation and the level of education of the subjects.